Development and psychometric testing of the family caregiver self-efficacy scale for patients in the early post-coronary artery bypass grafting. - Shiqi Zhou; Yinghong Zhang; Yuting Liu; Qi Yang; Pan Peng; Li Geng; Liu Hu (PLoS ONE)
Background and objectives Family caregiver self-efficacy plays an important role in improving the health and quality of life of patients in the early post-coronary artery bypass grafting (CABG). However, there is a lack of targeted self-efficacy assessment tool for caregivers of patients. Thus, the purpose of this study was to develop a Family Caregiver Self-Efficacy Scale for patients in the early post-CABG (FCSES-EPCABG) and to test its reliability and validity. Methods Based on self-efficacy theory, the initial scale was formed by the literature review, semi-structured interviews, Delphi expert consultation, and pre-survey. Through the convenience sampling method, 133 caregivers who met the selection criteria were chosen for the questionnaire survey at Wuhan Asian Heart Hospital from January 2024 to May 2024. The aim was to test the reliability and validity of the scale. Results The final scale contained five dimensions of wound care, medication management, cardiac rehabilitation management, social support, and self-care, with a total of 22 items. The item-level content validity index ranged from 0.889 to 1.000, the scale-level content validity index/average was 0.985, and the content validity ratio ranged from 0.778 to 1.000. The exploratory factor analysis showed that the cumulative variance contribution rate of the five dimensions was 69.433%. In the criterion-related validity analysis, the total score of the FCSES-EPCABG was positively correlated with the total score of the General Self-Efficacy Scale (r = 0.762, P<0.001). The Cronbach's alpha coefficient of the scale was 0.919, the half reliability was 0.779, and the test-retest reliability was 0.936. Conclusion The FCSES-EPCABG has satisfactory reliability and validity, which is suitable for evaluating the self-efficacy of family caregivers of patients in the early post-CABG.